Features of Motion and Heat Transfer of Swirling Flows in Channels of Complex Geometry - Sergey Dmitriev; Alexey Sobornov; Andrey Kurkin (Fluids)
The computational and experimental study results of swirling single-phase coolant motion and heat transfer for the standard operation parameters of a nuclear power plant are presented. The experimental model is a vertical heat exchanger of a “pipe in a pipe” type with the countercurrent movement of coolants. Six different swirlers (three with a constant twist pitch and three with a variable pitch) were considered. The heat exchanger temperature field was measured at various combinations of coolant flow rates, and a channel pressure drop for each swirl was determined. Computational studies were performed using the Omega-based Reynolds stress model and SST model with a correction for curvature streamlines. A good agreement between numerical and experimental data was obtained. Based on the velocity and temperature fields, swirling flow motion features in channels with a variable swirl pitch were discovered. For each intensifier, the effectiveness criterion in comparison with a pipe channel was determined.